PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR TEMATIK INTEGRATIF PESERTA DIDIK KELAS V SD NEGERI KARANGPELEM 1 TAHUN PELAJARAN 2021/2022 - Wulandari, Nita; Hartini, Sri; Mustofa, Mukhlis (JURNAL SINEKTIK, 2023)
The purpose of this study was to determine the effect of the STAD type cooperative learning model assisted by video learning on the thematic learning outcomes of integraphy in fifth grade students of SD Negeri Karangpelem 1 Academic Year 2021/2022. This research is a quantitative research with a pre-experimental method, the research design is one group pretest-posttest design. The population in this study were all fifth grade students of SD Negeri Karangpelem 1, totaling 34 students. The sampling technique used is saturated sampling because all the population is used as a sample. Data collection techniques using tests, observations, and documentation. Test the validity of the data sought by biserial point correlation. The data analysis technique was searched through normality test using the Kolmogorov Smirnov method and hypothesis testing using the Paired Sample T-Test formula. Based on the results of data analysis using paired sample t-test, the results obtained with a value, tcount of 14.707. So it can be concluded that the results of tcount = 14.707 more than ttable at the 5% significance level = 14.707 or tcount > ttable = 14.707 > 2.034 then Ho is rejected and Ha is accepted. Thus the hypothesis which states that: "there is an effect of the STAD type cooperative learning model assisted by video learning on the thematic integrative learning outcomes of fifth grade students of SD Negeri Karangpelem 1 Academic Year 2021/2022" is proven true at a significance level of 5%.